Use of tactical radio operator’s vital signs as context information for dynamic spectrum management within MANETs - Joanna Głowacka; Piotr Gajewski; Michał Ciołek; Krzysztof Parobczak; Jarosław Wojtuń (EAI Endorsed Transactions on Wireless Spectrum, 2020)
INTRODUCTION: The Authors present a new approach to a method of dynamic spectrum management for militarymobile ad hoc network. They propose that data concerning vital signs of tactical radio operators be used as contextinformation for spectrum management. If the operator’s inability to operate and protect the tactical radio is identified,actions (remote control of radio) are taken with the aim to release spectrum resources which used by the radio.Additionally, in this case remote control of radio allows switch the radio to modes used by search and rescue teams andlock the radio for unauthorized person.OBJECTIVES: The primary objective of this study was use vital signs of tactical radio operator’s as context informationfor dynamic spectrum management within MANET.METHODS: Tests for correct detection of vital signs were carried out for data generated on a Hal S3201 adult patientsimulator. Hypotheses about radio operator's vital signs were verified by means of a belief function defined in DempsterShafer theory.RESULTS: Loss vital signs by the operator allows to remote turn off his/her tactical radio while allocating more resourcesto other network users, which allow increasing data throughput.CONCLUSION: Monitoring vital signs of a tactical radio operator enables detecting combat readiness loss which resultsin inability to protect communications and can be used in spectrum management mechanisms.